Allergic Reactions and Cross-Reactivity Potential with Beta-Lactamase Inhibitors - Kayla R. Stover; Katie E. Barber; Jamie L. Wagner (MDPI AG, 2019)
Although beta-lactam allergies are an emerging focus of stewardship programs and interventions, less is publicly released regarding allergies to beta-lactamase inhibitors. This review presents and evaluates the data regarding allergic reactions with beta-lactamase inhibitors. Clavulanate, sulbactam, and tazobactam are beta-lactam-based beta-lactamase inhibitors that are combined with several penicillins or cephalosporins in order to preserve antimicrobial activity in the presence of beta-lactamases. Avibactam, relebactam, and vaborbactam are non-beta-lactam beta-lactamase inhibitors that are combined with cephalosporins or carbapenems in order to expand the antimicrobial activity against broader-spectrum beta-lactamases. Case reports document hypersensitivity reactions to clavulanate, sulbactam, and tazobactam, but not to avibactam, relebactam, or vaborbactam. Based on these reports and considering the chemical structures, cross-allergenicity with beta-lactams is likely with sulbactam and tazobactam. Considering the slightly altered beta-lactam structure, cross-allergenicity is less likely with clavulanate, but still possible. It appears that cross-allergenicity between beta-lactam antimicrobials and the newer, non-beta-lactam beta-lactamase inhibitors is unlikely. It is important for clinicians to perform allergy testing to both the beta-lactam and the beta-lactamase inhibitor in order to confirm the specific allergy and reaction type.